# Maria determined that these expressions are equivalent expressions using the values of x=3 and x=7. Which statements are true. Check all that apply

###### Question:

## Answers

D, F, G / 4, 6, 7

Step-by-step explanation:

We have the following equations:

5 + 3x - 2 and x + 2(x+1) + 1

Before checking the statements. Let's solve the syste of equations:

5 + 3x - 2 = x + 2(x+1) + 1

5 + 3x - 2 = x + 2x+2 + 1

3x + 3 = 3x + 3

Both equations are equivalent. Now, let's judge the statements:

1. The expressions are only equivalent when evaluated with odd values.

Given that the both expression are the same, the expressions are equivalent for ALL values.

Therefore, the statement IS FALSE ❌

2. The expressions are only equivalent for x=3 and x=7.

Given that the both expression are the same, the expressions are equivalent for ALL values, not only x=3 and x=7.

Therefore, the statement IS FALSE ❌

3. The expressions should have been evaluated with one odd value and one even value.

If two expressions are equivalent, they should be equivalent for ALL values. Sometimes, evaluating just one odd and one even value isn't enough. That's why the best approach is to solve the system of equations.

Therefore, the statement IS FALSE ❌

4. The expressions have equivalent values when x=6.

Given that the both expression are the same, the expressions are equivalent for x=6 (And all the real values too).

Therefore, the statement IS TRUE ✅

5. When x=0, the first expression has a value of 3 and the second expression has a value of 4.

Given that BOTH expressions are equvalent, they have the same value when x=0, which is 3.

Therefore, the statement IS FALSE ❌

6. The expressions have equivalent values for any value of x.

Given that the both expression are the same, the expressions are equivalent for ALL values of x.

Therefore, the statement IS TRUE ✅

7. When x=10, both expressions have a value of 33

Given that the both expression are the same, the expressions are equivalent for ALL values of x. That's why when x=0, both expressions have a value of 33.

Therefore, the statement IS TRUE ✅

8-2+2x1+1=10 is the answer

Step-by-step explanation:

D,F,G

Step-by-step explanation:

It Makes Sense.

Explanation:

1) X=2(x+1)+1 is the true statement

idk mam

Explanation:

it answer is 300

Photo :)

Step-by-step explanation:

Got it right :))

[tex]Maria determined that these expressions are equivalent expressions using the values of x = 3 and x =[/tex]

this doesn't give me a reason to check off

We have the following equations:

5 + 3x - 2 and x + 2(x+1) + 1

Before checking the statements. Let's solve the syste of equations:

5 + 3x - 2 = x + 2(x+1) + 1

5 + 3x - 2 = x + 2x+2 + 1

3x + 3 = 3x + 3

Both equations are equivalent. Now, let's judge the statements:

1. The expressions are only equivalent when evaluated with odd values.

Given that the both expression are the same, the expressions are equivalent for ALL values.

Therefore, the statement IS FALSE ❌

2. The expressions are only equivalent for x=3 and x=7.

Given that the both expression are the same, the expressions are equivalent for ALL values, not only x=3 and x=7.

Therefore, the statement IS FALSE ❌

3. The expressions should have been evaluated with one odd value and one even value.

If two expressions are equivalent, they should be equivalent for ALL values. Sometimes, evaluating just one odd and one even value isn't enough. That's why the best approach is to solve the system of equations.

Therefore, the statement IS FALSE ❌

4. The expressions have equivalent values when x=6.

Given that the both expression are the same, the expressions are equivalent for x=6 (And all the real values too).

Therefore, the statement IS TRUE ✅

5. When x=0, the first expression has a value of 3 and the second expression has a value of 4.

Given that BOTH expressions are equvalent, they have the same value when x=0, which is 3.

Therefore, the statement IS FALSE ❌

6. The expressions have equivalent values for any value of x.

Given that the both expression are the same, the expressions are equivalent for ALL values of x.

Therefore, the statement IS TRUE ✅

7. When x=10, both expressions have a value of 33

Given that the both expression are the same, the expressions are equivalent for ALL values of x. That's why when x=0, both expressions have a value of 33.

Therefore, the statement IS TRUE ✅

Where is the picture?

Step-by-step explanation:

yes

step-by-step explanation:

wfirfkfr/jjfi; jn; p/ojkfvlbvmkmgkgkkkgkkg

step-by-step explanation: